Synthesizing redox biogeochemistry at aquatic interfaces - Lau, Maximilian Peter; Niederdorfer, Robert; Sepulveda-Jauregui, Armando; Hupfer, Michael (My University, 2018)
The exchange of matter and energy between confined components of aquatic ecosystems requires the passage through their interfaces. This passage is characterized by rapid changes in physical, chemical and biological conditions and often triggers chemical transformations that involve the exchange of electrons: redox reactions. Over the last decades, research in aquatic biogeochemistry has resulted in many new but conceptually isolated findings that, together, frame an emergent view on the overarching principles of aquatic redox processes. A thermodynamic assessment may reveal the maximum available energy from such redox reactions. However, this energy can rarely be released due to various morphological, ecological and kinetic constrains on the turnover reactions. As these constrains set the boundary conditions for aquatic ecosystem functioning, they deserve particular attention in freshwater research. Here, we illustrate how physical and structural traits shape a complex redox environment and how this environment ultimately exercises control on the inhabiting microbial community and its metabolism. This aquatic microbiome is the key entity of material turnover. At the same time, the biome possesses the capability to feed back on its environment by shaping the local redox conditions and sustain niche existences. We discuss current and emerging ideas of how microorganisms engineer their environment, affecting aquatic redox reactions. In total, we examine this feed-back cycling between the physical environment and its colonizing biome to encourage the reader to take on the redox perspective when analyzing processes at aquatic interfaces. Understanding electron fluxes on both temporal and spatial scales is essential for the overall comprehension of matter and energy fluxes through freshwater environments. We pinpoint the methodological frontiers that will need to be challenged in future studies of aquatic redox processes. An improved mechanistic understanding will be instrumental in estimating sink and source properties of aquatic ecosystems.
Keywords: aquatic redox chemistry; thermodynamics; microbial ecology; microbial respiration; sediments; biofilms